The Movement of IDX Agriculture (JKAGRI) During the Covid-19 Pandemic - Nerisa Agnesia Widianto; Khotim Fadhli; Purbowo Purbowo (INDEF - Institute for Development of Economics and Finance, 2021)
The Covid-19 pandemic caused a drastic correction in the Jakarta Composite Index (JCI) during the first quarter of 2020. This study analyzes the factors that influence the movement of IDX Agriculture (JKAGRI) during the pandemic in 2020. The study used secondary data (time series) obtained from the sites Investing.com, then it was analyzed using multiple linear regression. The results showed that simultaneously the independent variables GOLD, NYSE, FCPO3, and USD/IDR significantly influence the JKAGRI. While partially the variable gold price (GOLD), New York Stock Exchange (NYSE), crude palm oil price index (FCPO3) have a significant effect on the movement of IDX Agriculture (JKAGRI). However, the dollar exchange rate (USD/IDR) does not significantly influence the movement of IDX Agriculture (JKAGRI). Thus, Traders are advised to closely monitor their portfolios while maintaining a stop loss at a certain percentage based on their risk profile. In contrast to investors who are expected to wait patiently for an increase or buyback to lower the average price (the average down) when technically indicates a price reversal signal. Keywords: Indonesian Stock Exchange, Agriculture, Regression, Investors JEL: G11, O24, Q14